Giant graviton expansions and ETW brane - Yasuyuki Hatsuda; Hai Lin; Tadashi Okazaki (Journal of High Energy Physics)
Abstract We study the giant gravitons in the AdS 4 bagpipe geometries involving end-of-the-world (ETW) brane constructed by a single 5-brane and either two stacks or one stack of D3-branes in Type IIB string theory. From the exact formulae and giant graviton expansions of the half-indices for the half-BPS boundary conditions and interfaces in N $$ \mathcal{N} $$ = 4 super Yang-Mills theory, we obtain the BPS spectra of the fluctuation modes of the AdS 4 bagpipe geometries including the ETW brane region.